Design of a Medical Record Management Information System Based on Long-Term Storage for Hospital Efficiency Using V-Model - Yuda Syahidin; Rena Novia Dewi Rena; Sali Setiatin (Indonesian Journal of Computer Science and Engineering, 2025)
This study aims to design an information system for the long-term storage of outpatient medical records in hospitals, focusing on improving data management efficiency, especially in retrieving inactive records. The research method used is descriptive with a qualitative approach. Data collection techniques include interviews, observations, and literature reviews. The software development process adopts the V-Model method, which emphasizes verification and validation at each development stage. The main problem identified in the long-term storage process is the manual classification of active and inactive records, which is done by checking the patient's last visit date one by one. This manual process is considered inefficient, time-consuming, and potentially disruptive to effective medical record management. To address this issue, the study proposes the design of an application that systematically manages inactive medical records in a computerized manner. This system is expected to help hospitals optimize time and resources, as well as support digital-based data storage policies. By implementing this information system, medical record management can become more structured, efficient, and accurate, ultimately enhancing the quality of health information services in hospitals.